Designing Performance Management System Using Balanced Scorecard and Competency-Based Approach: A Case Study At Perumda Air Minum Tirta Jaya Mandiri (PDAM) Kabupaten Sukabumi - Farhan Muhammad Raihan; Aurik Gustomo (Dinasti Review, 2026)
This study aims to design an integrated performance management system that links organizational strategy with individual performance and capability at Perumda Air Minum Tirta Jaya Mandiri Kabupaten Sukabumi. A qualitative case study approach was employed through semi-structured interviews with key management personnel and analysis of organizational documents. The data were analyzed using thematic analysis and triangulation to identify gaps between existing performance management practices and ideal system characteristics. The findings indicate that current performance appraisal practices remain administrative in nature and lack strategically cascaded KPIs and a structured competency framework. The proposed integration of the Balanced Scorecard and a competency-based approach enhances strategic alignment, objectivity, and transparency in employee performance evaluation.